Corrosion inhidition of inconel(600) in sodium chloride solution by sodium sulphate - Baghdad Science Journal (مجلة بغداد للعلوم)
a porentioncsisteve has been carried out of the corrosion behavior of inconel(600) in chloride ions (Cl) over the tempreatures 293 over the temperatures 308K in both the dcacrated and the alloy